Novel tools in cell and molecular biology: induced pluripotent stem cells in the field of lysosomal storage disorders - Amaral, Olga (2021)
Novel tools in cell and molecular biology: induced pluripotent stem cells in the field of lysosomal storage disorders - Invited lecture